Impact of aerosol direct effect on East Asian air quality during the EAST‐AIRE campaign. Issue 11 (2nd June 2016) - Wang, Jing; Allen, Dale J.; Pickering, Kenneth E.; Li, Zhanqing; He, Hao
Abstract: WRF‐Chem simulations were performed for the March 2005 East Asian Studies of Tropospheric Aerosols: an International Regional Experiment (EAST‐AIRE) Intensive Observation Campaign (IOC) to investigate the direct effects of aerosols on surface radiation and air quality. Domain‐wide, WRF‐Chem showed a decrease of 20 W/m 2 in surface shortwave (SW) radiation due to the aerosol direct effect (ADE), consistent with observational studies. The ADE caused 24 h surface PM2.5 (particulate matter with diameter < 2.5 µm) concentrations to increase in eastern China (4.4%), southern China (10%), western China (2.3%), and the Sichuan Basin (9.6%), due to different aerosol compositions in these four regions. Conversely, surface 1 h maximum ozone was reduced by 2.3% domain‐wide and up to 12% in eastern China because less radiation reached the surface. We also investigated the impact of reducing SO2 and black carbon (BC) emissions by 80% on aerosol amounts via two sensitivity simulations. Reducing SO2 decreased surface PM2.5 concentrations in the Sichuan Basin and southern China by 5.4% and decreased ozone by up to 6 ppbv in the Sichuan Basin and Southern China. Reducing BC emissions decreased PM2.5 by 3% in eastern China and the Sichuan Basin but increased surface ozone by up to 3.6 ppbv in eastern China and the Sichuan Basin. This study indicates that the benefits of reducing PM2.5 associated with reducing absorbing aerosols may be partially offset by increases in ozone at least for a scenario when NO x and VOC emissions are unchanged. Key Points: Modeled shortwave radiation at the surface over East Asia decreases by 20 W m‐2 due to the aerosol direct effect The aerosol direct effect causes modeled PM2.5 concentrations over East Asia to increase and ozone amounts to decrease PM2.5 air quality benefits in East Asia associated with reducing absorbing aerosols may be partially offset by increases in ozone